2020
DOI: 10.2337/dc20-1485
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum 25-Hydroxyvitamin D Concentrations With All-Cause and Cause-Specific Mortality Among Individuals With Diabetes

Abstract: OBJECTIVE The evidence regarding vitamin D status and mortality among people with diabetes is scarce. This study aimed to examine the association of serum 25-hydroxyvitamin D [25(OH)D] concentrations with all-cause and cause-specific mortality among adults with diabetes. RESEARCH DESIGN AND METHODS This study included 6,329 adults with diabetes from the Third National Health and Nutrition Examination Survey (NHANES III) and N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 35 publications
11
96
0
1
Order By: Relevance
“…A recent Brazilian cohort showed that patients with good glycemic control had higher VD levels [32]. A study on more than 6000 people with diabetes also found a strong association between low HbA1c level and high VD concentration, also in connection with a decrease in insulin resistance [33]. In particular, we noted a decrease in insulin resistance in diabetic patients treated with VD, and thus an improvement in glycemic control [34,35].…”
Section: Discussionsupporting
confidence: 72%
“…A recent Brazilian cohort showed that patients with good glycemic control had higher VD levels [32]. A study on more than 6000 people with diabetes also found a strong association between low HbA1c level and high VD concentration, also in connection with a decrease in insulin resistance [33]. In particular, we noted a decrease in insulin resistance in diabetic patients treated with VD, and thus an improvement in glycemic control [34,35].…”
Section: Discussionsupporting
confidence: 72%
“…Higher levels of 25(OH)D are associated with lower overall cancer risk [ 13 ]. Higher levels of 25(OH)D are also associated with lower all-cause mortality and cardiovascular disease mortality in patients with diabetes [ 14 ]. However, vitamin D insufficiency or deficiency is relatively common in Chinese children and adolescents [ 15 ] and postmenopausal women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have also linked vitamin D deficiency to the occurrence of chronic complications associated with T2D such as macrovascular and microvascular complications and overall mortality [106,107], suggesting that the maintenance of adequate vitamin D status may reduce the risk of mortality in people with diabetes. However, the nature of these studies does not allow us to draw causal conclusions, so we can only speculate about the different associations.…”
Section: Vitamin D Status and T2dmentioning
confidence: 99%